2017
DOI: 10.1038/s41598-017-07845-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent motor dysfunction due to neuron-specific disruption of stress-activated protein kinase MKK7

Abstract: c-Jun N-terminal kinase (JNK) is a member of the mitogen-activated protein kinase family and controls various physiological processes including apoptosis. A specific upstream activator of JNKs is the mitogen-activated protein kinase kinase 7 (MKK7). It has been reported that MKK7-JNK signaling plays an important regulatory role in neural development, however, post-developmental functions in the nervous system have not been elucidated. In this study, we generated neuron-specific Mkk7 knockout mice (MKK7 cKO), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
2
14
0
1
Order By: Relevance
“…We also observed enlarged, strongly pS6-positive neurons in other brain regions including the thalamus and amygdala (Supplemental Fig. 1), but not in the caudate and putamen due to relatively sparse Cre expression in the striatum, as previously shown (Yamasaki et al, 2017). These findings strongly indicate that Depdc5 loss in neurons throughout the majority of the brain results in mTORC1 hyperactivation.…”
Section: Resultssupporting
confidence: 86%
“…We also observed enlarged, strongly pS6-positive neurons in other brain regions including the thalamus and amygdala (Supplemental Fig. 1), but not in the caudate and putamen due to relatively sparse Cre expression in the striatum, as previously shown (Yamasaki et al, 2017). These findings strongly indicate that Depdc5 loss in neurons throughout the majority of the brain results in mTORC1 hyperactivation.…”
Section: Resultssupporting
confidence: 86%
“…We also identified the upstream signal that activates JNK. In the brain, MKK7 is a specific activator of JNK ( Yamasaki et al., 2011 ), and mice with brain-specific conditional knockout (cKO) of MKK7 exhibit hypoactive axon formation in the developing brain ( Yamasaki et al., 2011 , Yamasaki et al., 2017 ). Using our phospho-specific Abs in this cKO mouse, we found that phosphorylation signals in the brain were greatly diminished, as also observed with the chemical inhibitor ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that neuron‐specific Mkk7 ‐deficient mice ( Mkk7 flox/flox Syn‐Cre mice, hereafter designated cKO mice) were born at the expected Mendelian ratio and were fertile (Yamasaki et al., 2017). During our regular maintenance of these animals, however, we noted that we rarely obtained pups from cKO female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Mice homozygous for the targeted (floxed) Mkk7 allele were previously described (Schramek et al., 2011), as were neuron‐specific Cre deleter strain Synapsin‐Cre ( Syn‐Cre ) transgenic mice on a C57BL/6 background (Zhu et al., 2001). The generation of Mkk7 flox/flox Syn‐Cre mice was described in our previous report (Yamasaki et al., 2017). ROSA‐tdTomato mice on the C57BL/6 background [B6.Cg‐Gt(ROSA)26Sortm9(CAG‐tdTomato)Hze/J] were originally obtained from the Jackson laboratory (Madisen et al., 2010) and maintained at the Mouse Facility of Tokyo Medical and Dental University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation